1999
DOI: 10.3168/jds.s0022-0302(99)75391-9
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Oxygen Species and Lipid Peroxidation Product-Scavenging Ability of Yogurt Organisms

Abstract: The antioxidative activity of the intracellular extracts of yogurt organisms was investigated. All 11 strains tested, including five strains of Streptococcus thermophilus and six strains of Lactobacillus delbrueckii ssp. bulgaricus, demonstrated an antioxidative effect on the inhibition of linoleic acid peroxidation. The antioxidative effect of intracellular extracts of 10(8) cells of yogurt organisms was equivalent to 25 to 96 ppm butylated hydroxytoluene, which indicated that all strains demonstrated excelle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 19 publications
3
25
0
2
Order By: Relevance
“…In this work, the in vitro antioxidant activity of the food isolated enterococci was observed by different methods, although the radical scavenging effect was only observed for culture supernatants. On contrast, free radical scavenging activity was described to intracellular extracts of some LAB, such as Lactobacillus delbrueckii (Lin and Yen, 1999), Lactobacillus acidophilus and Bifidobacterium longum (Lin and Chang, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, the in vitro antioxidant activity of the food isolated enterococci was observed by different methods, although the radical scavenging effect was only observed for culture supernatants. On contrast, free radical scavenging activity was described to intracellular extracts of some LAB, such as Lactobacillus delbrueckii (Lin and Yen, 1999), Lactobacillus acidophilus and Bifidobacterium longum (Lin and Chang, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The antioxidant activity of some species of LAB has been demonstrated by in vitro enzymatic assays (Lin and Yen, 1999). The capacity to accumulate selenite (Se 4+ ), an essential element showing antioxidant properties (Thirunavukkarasu et al, 2004) has been described for some isolates of Enterococcus (Pieniz et al, 2011) and other LAB (Svoboda et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A few in vitro studies have reported that these bacteria or their extracts show a scavenging ability for lipid peroxidation products (malondialdehyde [MDA]) and also that they are able to protect plasma against lipid peroxidation (27)(28)(29).…”
mentioning
confidence: 99%
“…The anti-oxidative effect of lactic acid bacteria has been reported [18]. Both of the bacterial strains used in this study, S. thermophilus 1131 and L. bulgaricus 2038, showed production of radical scavengers and inhibited oxidation of erythrocyte membranes and low-density lipoprotein in vitro [40].…”
Section: Discussionmentioning
confidence: 96%